The Choice of Financing Instrument in Game Companies: With Study on Finnish Start-ups - Riippi, Juulia (2024)
This study explores the funding choices of game companies in Finland, focusing on understanding the reasons behind these choices. The game industry is a growing industry, and Finland is an attractive country for the industry’s international employees, as well as for international investors. The game industry is a significant cultural export industry for Finland, and external funding is crucial for its growth.